Digging Deeper: Global Coal Prices and Industrial Growth, 1840-1960 - Wegerich, A (2016)
This thesis investigates to what extent coal prices differed globally during the nineteenth and twentieth centuries, and whether those differences mattered for economic development. The backbone of my empirical investigation is a new dataset of annual coal prices spanning the years 1840 to 1960 for, on average, over 30 globally distributed ports. This dataset is complemented by pithead prices for all major coal-producing countries. My analysis includes all major steam coals and I eliminate quality differences by accounting for differences in their carbon content. I construct my argument by examining two major drivers of differences in coal prices. First, I examine trade costs for Welsh steam coals, which were shipped to most regions of the world. Secondly, I estimate the effect of the spread of coal mining, for example to India, on local coal prices by initating competition between coals from different origins. While trade costs declined most during the late nineteenth century, the spread of coal mining led to continued price convergence in the interwar period. And yet, global coal price differences remained significant, especially between producing and importing countries. Arguably, my most interesting finding is on the effect of those coal price differences. More specifically, I calculate the ratio of coal prices to wages, and explore whether countries where this ratio was closer to the British ratio were in the best position to use the most advanced steam technology. My econometric results indeed show that countries with a low coal price/wage ratio experienced higher manufacturing output growth during the period 1870 to 1940. This finding of my thesis highlights one potential way in which different levels of coal prices may have contributed to varying degrees of technology adoption between countries and ultimately economic growth.